Mandatory national quality improvement systems using indicators: an initial assessment in Europe and Israel - Bramesfeld, Anke; Szecsenyi, Joachim (Health policy, 2016)
Quality improvement systems (QIS) that are based on empirical performance assessment have increasingly been implemented as a mandatory part of health systems across countries. This study aims to describe national mandatory QIS in Europe in 2014. Relevant national agencies for national mandatory QIS in Europe were identified through online searches and key informants. A questionnaire was compiled during a workshop with these agencies and filled out by representatives from these particular agencies. Agencies in charge of national mandatory QIS in seven countries (Denmark, France, Germany, Israel, Scotland, Sweden and Switzerland) were included in the study. An analysis of QIS revealed similarities, such as the use of routine data for performance assessment and the aim to hold healthcare providers accountable. Differences relate to the different forms of feedback systems and improvement mechanisms used. Trends include the development towards greater implementation of QIS within health systems, the inclusion of the patient’s perspective in performance assessment, and experiments with pay for performance-related measures. On a country level, for health systems striving for newly implementing QIS it is recommended to start where routine data is available, add qualitative methodologies once the QIS is getting more complex, report performance data back to service providers and be patient centred. On the inter-country level exchange of information between agencies commissioned with implementing national QIS is very much needed for 1.Better understanding the other systems;2.Gaining inspiration;3.Working towards obtaining better evidence on the impact that the different tools used and measures taken by national QIS have on the quality of care at health system level.
Gesehen am 11.10.2017